PROCEEDINGS OF XV CONGRESSO BRASILEIRO DE TRANSPLANTES; XVI CONGRESSO LUSO BRASILEIRO DE TRANSPLANTES; XIV ENCONTRO DE ENFERMAGEM EM TRANSPLANTES AND FÓRUM DE HISTOCOMPATIBILIDADE DA ABH - ABTO, Associação Brasileira de Transplantes de Órgãos (Brazilian Journal of Transplantation, 2018)
In this issue are presented abstracts of: LIVER; NURSING AND IMMUNO/HISTO/TISSUE.